'IT'S CIVILITY!': A Portrait of Modernization and the Pedagogy of Bodies by the Press of Franca (1890-1940) - Lopes, Gabriel [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2023)
The final decades of the 19th century and the beginning of the 20th century saw political, economic and social changes in a Brazil that was becoming republican. In the cities, hygienist projects despoiled the most vulnerable sections of the population in exchange for beautifying the city. Assuming a comprehensive conception of the educational process, it is possible to glimpse in the media and in the legislation -more precisely, in the press and in the 1910 Municipal Code of Franca, our objects of study -an exercise in the pedagogy of bodies, assuming a Foucauldian point of analysis. In fact, the printing press played a leading role in this plot to educate a rural population that was becoming urban. The aim of this paper rests on this formulation, identifying in the selected local periodicals and in the legislative code ways of representing a portrait of this domain of gestures.
Keywords: Modernization; Press; Power; Pedagogy of Bodies; Docile Bodies